Metal from heaven : a confession at the end - Clarke, H. A., 1997- (Erewhon, an imprint of Kensington Publishing Corp., 2024)
"He who controls ichorite controls the world. A malleable metal more durable than steel, ichorite is a toxic natural resource fueling national growth, and ambitious industrialist Yann Chauncey helms production of this miraculous ore. Working his foundry is an underclass of destitute workers, struggling to get better wages and proper medical treatment for those exposed to ichorite's debilitating effects since birth. One of those luster-touched victims, the child worker Marney Honeycutt, is picketing with her family and best friend when a bloody tragedy unfolds. Chauncey's strikebreakers open fire. Only Marney survives. A decade later, as Yann Chauncey searches for a suitable political marriage for his ward, Marney sees the perfect opportunity for revenge. With the help of radical bandits and their stolen wealth, she must masquerade as an aristocrat to win over the calculating Gossamer Chauncey and kill the man who slaughtered her family and friends. But she is not the only suitor after Lady Gossamer's hand, leading her to play twisted elitist games of intrigue. And Marney's luster-touched connection to the mysterious resource and its foundry might put her in grave danger - or save her from it." --